KONSERVASI LINGKUNGAN DALAM DESA MULTIKULTURAL PERSPEKTIF AL-QUR’AN: Studi Living Qur’an di Desa Reco, Wonosobo. - Widodo Hami; Akhmad Aufa Syukron; Muhammad Al Fatih (STAI AL-ANWAR SARANG, 2025)
The current environmental crisis still requires special attention from all parties considering that the impacts will be felt globally. All religions, including Islam, Christianity, Judaism, Hinduism, Buddhism and others, also have a crucial role in maintaining environmental conservation. Through teachings, religion is believed to be able to be a power to always preserve the environment. This has been proven by the people of Reco Kertek Village, Wonosobo, who consistently maintain environmental sustainability in the Mount Sindoro area so that it becomes a tourist destination with its natural beauty. The purpose of this study is to reveal how environmental conservation is carried out by the multi-cultural community of Reco Village and how they use the Qur'an as an inspiration for environmental conservation. The methodology used in this study is a qualitative field-based methodology (field research) with the object of research in Reco Village, Kertek District, Wonosobo Regency, using phenomenology as its approach based on Petter L Berger's social construction theory. With this methodology and approach, this study succeeded in revealing the finding that the spirit of the Qur'an implemented by the Reco community was able to motivate them to carry out environmental conservation programs, including the Mountain Belt Program, Basecamp Management, and social community activities.. The Reco Village community bases their conservation spirit on QS Al-Rum: 41 and QS Al-A’raf: 10 which state that the destruction of nature is caused by human actions, whereas nature itself provides many benefits for human life.